Indonesian radiology research metrics and their alignment with the sustainable development goals - Mukmin, Amril (Riset Informasi Kesehatan, 2026)
Background: Radiology is one of the most dynamic and essential fields in modern medicine. However, few studies have systematically examined the development trends, terminology, and contributions of Indonesian radiology literature to the achievement of the Sustainable Development Goals (SDGs). This study aims to analyze bibliometric trends and the alignment of Indonesian radiology research with the SDGs from 2015 to mid-2025. Method: This study utilized a bibliometric review with assistance by three main tools: Bibliometrix R Package, VOSviewer, and SDGs Mapper. Results: The results reveal fluctuating publication trends and a general decline in annual citation rates. Atom Indonesia emerged as the most prolific source, while the Bali Medical Journal has shown increased contributions in recent years. The most productive author was Oscandar F., followed by Yusra, noted for cross-institutional collaboration. Universitas Indonesia led in publication volume, and the article by Saktiawati et al. (1) received the highest citations. The United Kingdom was the most frequent international collaborator. Key thematic focuses included “tuberculosis,” “diagnostic imaging,” and “thorax radiography,” with emerging topics such as “orthopedics” and “cancer risk.” Notably, 83.2% of SDG-related publications contributed to SDG 3, underscoring the centrality of health issues in national radiology research. Conclusion: In sum, this study offered a comprehensive overview of the Indonesian radiology research landscape and its relevance to sustainable development goals.